Applications of the Lie symmetries to complete solution of a bead on a rotating wire hoop - Basquerotto, Cláudio H. C. Costa [UNESP]; Righetto, Edison [UNESP]; Silva, Samuel da [UNESP] (Springer Nature, 2018)
The existence of Lie symmetries in differential equations can generate transformations in the dependent and independent variables and obtain new equations that may be easier to integrate. In particular, in some situations, one can reduce the order and it is possible to obtain first integrals. Thus, this article presents the application of the fundamental Lie theorem to obtain the complete solution of a classical nonlinear problem of the dynamics of mechanical systems: the bead on a rotating wire hoop. From the first integral obtained with the Lie symmetry generators, the exact solution can be found with the aid of the Jacobi elliptic functions.
Keywords: Classical mechanics; Jacobi elliptic functions; Lie symmetries